Formulasi Gel Kombinasi Lendir Bekicot (Achatina fulica Ferr) dan Lidah Buaya (Aloe vera) sebagai Bahan Aktif untuk Terapi Luka Bakar - Pudiastuti RSP; Siti Aisiyah (Jurnal Farmasi Indonesia, 2014)
The use of natural materials as active materials in the treatment of benefits in addition to minimizing the adverse effects of natural materials also tend to be cheaper and easier to obtain. The aloe vera plant and snail slime proved to be used in the treatment of burn. Aloe vera contains potent compounds such as fats, carbohydrates, proteins, amino acids, minerals and enzymes Section meat has been widely used for the topical treatment of wounds, burns and skin irritation. Aloe vera can stimulate wound healing because it can increase the formation of collagen in skin tissue The use of snail slime and aloe vera directly considered less practical, so that made gel preparation. Selection of the appropriate base in a formulation will determine the ease or not the drug / active substance effect. Snail mucus gel formulation and a combination of aloe vera are made with a variety of combinations of active ingredients used in the total amount of active ingredient as much as 4%. The resulting gel in physical properties include organoleptic test, viscosity, dispersive power, shifting the viscosity and the antibacterial activity with the diffusion method. The test results were analyzed statistics one-way ANOVA test and Tukey's t-test with a level of 95%. The results showed that all three formulas give viscosity, dispersive power and adhesion are not significantly different. Results of tests performed for 4 weeks showed three formulas provide a stable gel preparation.